2021
DOI: 10.3390/ijerph18147618
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Inserted Central Catheter Placement in a Cardiology Ward: A Focus Group Study of Nurses’ Perspectives

Abstract: Intravenous therapy administration through peripheral venous catheters is one of the most common nursing procedures performed in clinical contexts. However, peripherally inserted central catheters (PICC) remain insufficiently used by nurses and can be considered a potential alternative for patients who need aggressive intravenous therapy and/or therapy for extended periods. The purpose of this study was to understand nurses’ perspectives about PICC implementation in their clinical practice. As part of an actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Previous authors have identified that the lack of an evidenced-informed standard of care could partially explain the unstandardized practices reported across the country [ 16 , 17 , 18 , 19 ]. This is especially true for Portuguese nurses, who are in charge of all aspects of PIVC care in the country, from device insertion to maintenance and surveillance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have identified that the lack of an evidenced-informed standard of care could partially explain the unstandardized practices reported across the country [ 16 , 17 , 18 , 19 ]. This is especially true for Portuguese nurses, who are in charge of all aspects of PIVC care in the country, from device insertion to maintenance and surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for Portuguese nurses, who are in charge of all aspects of PIVC care in the country, from device insertion to maintenance and surveillance. [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies found similar response rates from nurses who agreed that PICC training was fundamental to delivering quality patient care (Jarding & Flynn Makic, 2021;Salgueiro-Oliveira et al, 2021). Furthermore, nurses believe that more education and training on PICC line indications and maintenance can help decrease infection incidences and increase patient satisfaction (Jarding & Flynn Makic, 2021;Salgueiro-Oliveira et al, 2021;Xu et al, 2020a).…”
Section: The Role Of the Registered Nursementioning
confidence: 90%
“…The responsibility of the acute care registered nurse is to assess and identify a patient9s needs while implementing nurse-led initiatives to promote patient well-being. An example of a nurse-led initiative is a PICC line sterile dressing change (Jarding & Flynn Makic, 2021;Salgueiro-Oliveira et al, 2021;Xu et al, 2020b). In a cross-sectional study by Xu et al (2020b), a survey revealed that registered nurses scored at a low level of correct responses on PICC maintenance knowledge and training topics.…”
Section: The Role Of the Registered Nursementioning
confidence: 99%